Attribution analysis of hydrological drought after the impoundment of the Danjiangkou reservoir in the Hanjiang River Basin - Cheng Li; Yanping Qu; Tianliang Jiang; Furen Jiang; Qianfeng Wang; Xuejun Zhang; Xiaohua Xu (Journal of Hydrology: Regional Studies)
Study region: Hanjiang River Basin, China Study focus: Under the joint influences of human activities and climate change, droughts frequently occur in the Hanjiang River Basin (HRB). Quantifying the driving forces contribution on hydrological drought is crucial to enhance the early warning ability. This study employed the standardized streamflow index (SSI) to assess hydrological drought. The Soil and Water Assessment Tool (SWAT) model was utilized to reconstruct natural streamflow based on hydrological and meteorological data. By comparing the variations of drought characteristics in simulated and observed scenarios, the impacts of human activities and climate change to hydrological drought were quantified. New hydrological insights for the study region: The SWAT model is capable of effectively simulating the natural streamflow conditions of the HRB with NSE>0.7, R2>0.8, logNSE>0.7 and |PBIAS|<20 %. Hydrological drought has intensified as a prolonged duration and greater severity affected by human activities and climate change. During the whole impact period (1968–2022), the duration and severity increased by 66.22 % and 81.16 % compared to baseline period (1956–1967). The year 1991 is detected as the mutation point. From 1968–1990 climate change has been the main factor in exacerbating hydrological drought. Since 1991, the influence of human activities has gradually exceeded the influence of climate change. These findings provide valuable insights for watershed integrated water resources management and water security.